Purwarupa Pembangkit Listrik Tenaga Air Pico Hydro Dengan Regulator Untuk Lampu Jalan Dan Port USB Charger - Jutri Bonal; Wendy Yuniarto; Agus Riyanto (Jurnal Serambi Engineering, 2025)
Nanga Bayan Village, tucked away in the beautiful Ketungau Hulu Sub-district of Sintang Regency, West Kalimantan, is a place full of natural wonders. It's home to stunning waterfalls, and while it's still working through some challenges with infrastructure, including limited access to electricity, internet, and transportation, the community is strong and hopeful for a better future. We're working on a prototype of a Pico Hydro Power Plant (PLTAPH) that has a voltage stabilizer. We're hoping to create a renewable energy solution for street lighting and USB charging. The system uses a Pelton turbine made from 300 mm PVC pipe with 10 blades and a 6 mm nozzle to regulate water head and flow rate. The potential energy from a 1.5-meter water drop is lovingly harnessed with the help of a water pump to drive the turbine and rotate a 24V permanent magnet DC generator capable of producing up to 30 Watts at 1300 rpm. The street lighting system has a light sensor (LDR) to automatically control it, which is great for efficiency and the environment. This research also develops a learning module based on local potential and enhances researchers' understanding of sustainable renewable energy solutions.